COAGULATION ABNORMALITIES AND THROMBOTIC COMPLICATIONS IN COVID-19: A HEMATOLOGICAL PERSPECTIVE - Dr Shafaq Saleem; Dr Sarah Arif (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: COVID-19, caused by SARS-CoV-2, impacts the respiratory system and induces significant coagulation abnormalities and thrombotic complications, particularly in severe cases. This study evaluated these hematological changes and ‘their association with disease severity and outcomes’.Methods: ‘A retrospective observational study was conducted at Khyber Medical University’ from January 2023 to January 2024, involving 120 COVID-19 patients. Participants ‘were categorized into mild/moderate (n=80) and severe/critical (n=40) groups’. Demographics, laboratory parameters, coagulation profiles, and clinical outcomes were analyzed, and statistical comparisons were made between the groups.Results: Severe/critical cases showed significantly elevated D-dimer levels, prolonged PT and aPTT, increased fibrinogen levels, and reduced platelet counts compared to mild/moderate ‘cases (p < 0.001)’. ‘Inflammatory markers, including CRP, ferritin, and IL-6’, were markedly higher in the severe group (p < 0.001). Thrombotic complications, such as DVT (25%) and PE (18%), were more frequent in severe cases, alongside higher mortality (40% vs. 2.5%, p < 0.001). Vaccination was associated with reduced disease severity, highlighting its protective role.Conclusion: Coagulation abnormalities and thrombotic complications are strongly associated with COVID-19 severity. ‘Elevated markers, D-dimer and inflammatory cytokines, underscore the hypercoagulable and inflammatory state in severe cases’. These findings highlight the importance of early detection, proactive monitoring, and individualized anticoagulation strategies to improve outcomes in high-risk patients.